Deus Criou o Mundo e Nos Construímos o Conjunto Palmeiras: Quilombismo Urbano de Populações Afrodescendentes em Fortaleza-Ceará - Matias, Emanuela Ferreira (2019)
Conjunto Palmeiras is an afrodescendant majority neighborhood, having 45 years of history of struggles and resistance as a mark of the strength of the organized social movement, which fought and built its own urbanization. It is home to a population of 36, 599,000, of which 27,700 are called brown and black, according to the latest sense of the IBGE in 2010. Historically the neighborhood is known for urban social struggles, but does not bring the racial aspect, because the neighborhood is not recognized as a black territory, although its population is mostly black and suffers from social and spatial segregation that are directly linked to structural racism practiced by the state. In view of this, the main objective of this work is to highlight Conjunto Palmeiras as a neighborhood with an afrodescendant majority, recognizing the memory of its struggles and resistance, as the practice of urban quilombism, giving visibility to traditional populations of African matrix and the practice of Umbanda. In this way, we narrate the history of Conjunto Palmeiras from the perspective of other narrators not known from social research, blacks and blacks, highlighting the traditional terreiro populations, in this case the Umbanda, which marks the ancestral African influence in the territory. We use the research method of afrodescendence in which a relationship between the research subject and the research subject is established, starting from the recognition that the two are parts of the same set, the life experience of the research subject with the researched environment is intertwined. The theoretical contribution is based on Nascimento (1980), Ratts (2006), Cunha Junior (2002, 2004, 2015), Santos (2013), Moura (1993), Castro (1977), Sobrinho (2011), Barros and Rolnik (1995), among others. It is concluded that our largest ancestral African representation is Umbanda and that the social movement of Conjunto Palmeiras does not recognize the neighborhood as being mostly black. Therefore, it is necessary that we make the struggle that has as central agenda the struggle of afro-descendants and fight for public policies that favor the culture, identity and life of the blacks of Conjunto Palmeiras.